2020 25th International Conference on Pattern Recognition (ICPR) 2021
DOI: 10.1109/icpr48806.2021.9413281
|View full text |Cite
|
Sign up to set email alerts
|

FC-DCNN: A densely connected neural network for stereo estimation

Abstract: We propose a novel lightweight network for stereo estimation. Our network consists of a fully-convolutional densely connected neural network (FC-DCNN) that computes matching costs between rectified image pairs. Our FC-DCNN method learns expressive features and performs some simple but effective postprocessing steps. The densely connected layer structure connects the output of each layer to the input of each subsequent layer. This network structure and the fact that we do not use any fullyconnected layers or 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…Dominik et al . [HF21] proposed a lightweight fully convolutional densely connected neural network (FC‐DCNN) for stereo estimation. Cheng et al .…”
Section: Related Workmentioning
confidence: 99%
“…Dominik et al . [HF21] proposed a lightweight fully convolutional densely connected neural network (FC‐DCNN) for stereo estimation. Cheng et al .…”
Section: Related Workmentioning
confidence: 99%
“…Guo et al [23] proposed construction of the cost volume by group-wise correlation to enhance performance. Dominik et al [24] proposed a lightweight fully convolutional densely CNN for stereo estimation. Poggi et al [25] introduced weakly guided stereo matching, leveraging a small number of sparse yet reliable depth measurements retrieved from an external source for training.…”
Section: Related Workmentioning
confidence: 99%
“…Dominik et al. [24] proposed a lightweight fully convolutional densely CNN for stereo estimation. Poggi et al.…”
Section: Related Workmentioning
confidence: 99%
“…The method FC-DCNN [3] by D. Hirner and F. Fraundorfer is used as a baseline implementation for this method. There, it has been shown that replacing the feature extraction step with a deep learning approach in order to learn highly-dimensional and expressive features already outperforms traditional stereo methods such as SGM.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we extend upon this method in two ways: Adding a network structure to learn a better similarity function between image patches and adding a network structure that learns to complete the sparse disparity map instead of using handcrafted post-processing steps. We end up with a fully trainable method that outperforms the baseline method of FC-DCNN [3] in all evaluated datasets and is comparable with other state-of-the art deep-learning methods. The whole method split into every step is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%